Strengthening traditional competenciesof Mah Meri community for indigenous tourism service performance - Kunasekaran, Puvaneswaran; Gill, Sarjit S.; Ramachandran, Sridar; Talib, Ahmad Tarmizi; Prabhakaran, Sudesh (IDOSI Publications, 2017)
This paper presents the perception of the indigenous community on tourism development in their area. This study was conducted at Kampung Sungai Bumbon, Carey Island, Selangor populated by the Mah Meri community. Naturalistic inquiry which was used as the qualitative data collection method helped the researchers to understand the host-tourism relationship before conducting further investigation. The findings show that the traditional competencies are important for sustainable community development. The community also revealed that the outsiders’ influence is highly significant for the village to run the tourism activities successfully. However, the community feels that their culture and tourism business has been exploited by outsiders. The findings of this study will contribute to existing literature in the indigenous tourism field that could enhance the sector into a more profitable business for the indigenous communities in Malaysia.